Structural challenges in the health domain of the health system reform: A qualitative study - Zahra Alipour; Narges Eskandari; Mohammad Abbasi; Marziyeh Raisi; Sareh Bakouei (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND AND AIM: Considering that the Qom University of Medical Sciences was a pioneer to implement the health system reform (HSR) in the domain of health services and the lack of a study that has addressed the challenges and strategies to promote the HSR in the health domain, this study was designed to explain the structural challenges and its solutions in the health domain of the HSR in the city of Qom, Iran, 2017. MATERIALS AND METHODS: This study was a qualitative research. The health managers, the health-care providers, and the recipients of health services referring to the health centers in Qom were the participants in this study who were selected using the convenience sampling method. The data were collected using individual interviews and with the guidance of a semi-structured questionnaire. Collected data were analyzed by the qualitative content analysis method with an inductive approach. After extracting the challenges of the HSR in the health domain through a qualitative approach, these challenges were prioritized through Delphi's technique in terms of relevance and resolving strategies. RESULTS: From the perspective of the study participants, the structural challenges of HSR in the health domain in order of importance and priority included problems due to the SIB system, defects in the instructions, the disruptions caused by multitasking, poor service coverage, incomplete health-care packages, and the shortage of resources. CONCLUSION: According to the findings of this study, we hoped that the HSR in the health area can be improved to increase its success by modifying the guidelines and the coverage of services, modifying the SIB system, providing requires resources, completing the service packages, and solving the multitasking problem.